Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.3390/app9153040
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Nasometric Instrument Structure on Nasalance Score

Abstract: Owing to the development of medical technology, devices to assess resonance (hypernasality and hyponasality) which result from conditions such as cleft palate and brain injury are being studied. In general, nasometric instruments are used to support clinical judgments of these disorders. For conventional separation-type nasometric instruments, there is an acoustic feedback effect between oral and nasal sounds. Recently, a mask-type nasometric instrument was developed for acoustic feedback insensitivity, but it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Our own earlier pilot study conducted on a smaller group of people, together with the current research, has shown that it is reasonable to use language tests on modern digital nasometers even though they were developed for analogue devices [7]. However, as Woo and colleagues have shown, differences in measurement equipment can cause discrepancies of up to several percent, despite the same language tests being used [11]. This suggests that measurement standards should be checked and adjusted whenever there are significant changes in recording methods [12].…”
Section: Discussionmentioning
confidence: 82%
“…Our own earlier pilot study conducted on a smaller group of people, together with the current research, has shown that it is reasonable to use language tests on modern digital nasometers even though they were developed for analogue devices [7]. However, as Woo and colleagues have shown, differences in measurement equipment can cause discrepancies of up to several percent, despite the same language tests being used [11]. This suggests that measurement standards should be checked and adjusted whenever there are significant changes in recording methods [12].…”
Section: Discussionmentioning
confidence: 82%
“…Recent developments in medical technology have increased the interest in rehabilitation devices. Among them, diagnostic technologies and devices related to speech therapy are continuously being studied [ 1 , 2 , 3 , 4 , 5 , 6 , 7 ]. Speech sound disorder is the most common childhood communication disorder, and articulation is very closely related to speech sound disorder [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…If the issue is severe, the unclear pronunciation causes problems such as communication disorders, difficulties, and decreased quality of life. The diagnosis and treatment of speech sound disorders, including traditional tactile perception tests and methods based on the subjective judgment of speech-based speech therapists, have many limitations [ 5 ]. In articulation movement, which is a key factor in speech sound disorder, the position and tension of the tongue (i.e., lax, tense and aspirated consonants) are very important factors [ 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%